Hakikat Nilai Dalam Sistem Pendidikan Keluarga Di Jepang - Sri Sudarsih (Diponegoro University, 2021)
This study focuses on the family education system in Japan. Family education is very important because it becomes the basis for the formation of children's character. The purpose of this study is to describe the family education system in Japan and interpret it to find the nature of values in the system. This research is qualitative research related to the family education system in Japan. The family in this regard is a family that still instills values in the five basic relationships in the family. The method used is description and interpretation. The results achieved: traditional family education in Japan is able to shape the character of children who have strong personalities. A tough personality is a personality that is coveted by society and the state like the personality of a knight who always acts according to the norm. The values that are instilled are rooted in the customs and instincts of the community. This value underlies the five principles of relationship norms, namely the norm of the relationship between master and servant, father and son, husband and wife, brother and sister, and friends. These values are the values of obedience, honesty, loyalty, discipline, and responsibility. The values contained in the five relationships are moral values. Five principles of relationships that are carried out consistently will achieve harmony.